Hormonal Regulation - Nuraliev Ahrorbek; Lee Myungjae; Lee Jungjae; Jae Hanbin; Lee Seungjun; Lee Seungmin; Salimova Dildora Erkinovna (Zien Journals, 2023)
All of the biologically active compounds and substrates involved in the regulation of biochemical processes and functions, hormones play a special role. Hormones are organic substances that are formed in tissues of one type (endocrine glands, or endocrine glands), enter the blood, are transported along the bloodstream to tissues of another type (target tissue), where they exert their biological effect (regulate metabolism, behavior and physiological functions of the body, as well as cell growth, division and differentiation). Hormonal regulation is a general term for the regulatory effects of various hormones on body functions. Hormonal regulation arose at a certain stage of evolution, earlier than neuromodulation, and serves as a link between the central nervous system and body tissues. Hormonal regulation plays an important role in maintaining homeostasis and in adapting the body to changes in the external and internal environment.
Keywords: homeostasis; adapting; functions; regulation